Quantitative computed tomography-derived clusters: Redefining airway remodeling in asthmatic patients - Gupta, S; Hartley, R; Khan, U; Singapuri, A; Hargadon, B; Monteiro, W; Pavord, I; Sousa, A; Marshall, R; Subramanian, D; Parr, D; Entwisle, J; et al. (2014)
Background Asthma heterogeneity is multidimensional and requires additional tools to unravel its complexity. Computed tomography (CT)-assessed proximal airway remodeling and air trapping in asthmatic patients might provide new insights into underlying disease mechanisms. Objectives The aim of this study was to explore novel, quantitative, CT-determined asthma phenotypes. Methods Sixty-five asthmatic patients and 30 healthy subjects underwent detailed clinical, physiologic characterization and quantitative CT analysis. Factor and cluster analysis techniques were used to determine 3 novel, quantitative, CT-based asthma phenotypes. Results Patients with severe and mild-to-moderate asthma demonstrated smaller mean right upper lobe apical segmental bronchus (RB1) lumen volume (LV) in comparison with healthy control subjects (272.3 mm3 [SD, 112.6 mm3], 259.0 mm3 [SD, 53.3 mm3], 366.4 mm3 [SD, 195.3 mm3], respectively; P =.007) but no difference in RB1 wall volume (WV). Air trapping measured based on mean lung density expiratory/inspiratory ratio was greater in patients with severe and mild-to-moderate asthma compared with that seen in healthy control subjects (0.861 [SD, 0.05)], 0.866 [SD, 0.07], and 0.830 [SD, 0.06], respectively; P =.04). The fractal dimension of the segmented airway tree was less in asthmatic patients compared with that seen in control subjects (P =.007). Three novel, quantitative, CT-based asthma clusters were identified, all of which demonstrated air trapping. Cluster 1 demonstrates increased RB1 WV and RB1 LV but decreased RB1 percentage WV. On the contrary, cluster 3 subjects have the smallest RB1 WV and LV values but the highest RB1 percentage WV values. There is a lack of proximal airway remodeling in cluster 2 subjects. Conclusions Quantitative CT analysis provides a new perspective in asthma phenotyping, which might prove useful in patient selection for novel therapies. © 2013 American Academy of Allergy, Asthma and Immunology.